Justice Denied: Low Submission Rates of Sexual Assault Kits and the Predicting Variables. Issue 17 (September 2019) - Valentine, Julie L.; Sekula, L. Kathleen; Cook, Lawrence J.; Campbell, Rebecca; Colbert, Alison; Weedn, Victor W.
Following sexual assaults, victims are advised to seek health care services with forensic evidence collected and packaged in sexual assault kits (SAKs). This large ( N = 1, 874), retrospective study examined rates of SAK submissions by law enforcement to the state crime laboratory for analysis from 2010 to 2013 at four sites in a Western state in the United States with established sexual assault nurse examiner (SANE) programs. Variables of legal and extralegal characteristics in sexual assault cases were explored through generalized estimating equations (GEE) modeling to determine what factors statistically predicted SAK submissions. For submitted SAKs, the length of time between the dates of assault and dates of submission was categorized, and bivariate and multivariate analyses were calculated to discover legal and extralegal characteristics affecting time of submission. The study sites represented 40% of the state's law enforcement agencies and 65% of the state's population. Out of the 1, 874 SAKs in the study, only 38.2% were submitted by law enforcement to the state crime laboratory for analysis. When SAK submissions were examined based on time between assaults and submission dates, 22.8% were submitted within a year of the assault and 15.4% were submitted more than a year after the assault following media and community pressure for law enforcement agencies to submit SAKs in storage. Significant variability of SAK submission rates and the time submitted from the assault dates were found between the sites. Site location was found to be the main determinant of whether or not SAKs were submitted. The lack of SAK submissions for analysis results in justice denied for victims and raises public safety concerns. The finding that the location in which the sexual assault occurred was the primary factor on SAK submissions represents an inequity of justice.